Association of BDNF, HTR2A, TPH1, SLC6A4, and COMT polymorphisms with tDCS and escitalopram efficacy: ancillary analysis of a double-blind, placebo-controlled trial - Brunoni,Andre R. (2020)
Objective: We investigated whether single nucleotide polymorphisms (SNPs) associated with neuroplasticity and activity of monoamine neurotransmitters, such as the brain-derived neurotrophic factor (BDNF, rs6265), the serotonin transporter (SLC6A4, rs25531), the tryptophan hydroxylase 1 (TPH1, rs1800532), the 5-hydroxytryptamine receptor 2A (HTR2A, rs6311, rs6313, rs7997012), and the catechol-O-methyltransferase (COMT, rs4680) genes, are associated with efficacy of transcranial direct current stimulation (tDCS) in major depression. Methods: Data from the Escitalopram vs. Electrical Current Therapy for Treating Depression Clinical Study (ELECT-TDCS) were used. Participants were antidepressant-free at baseline and presented with an acute, moderate-to-severe unipolar depressive episode. They were randomized to receive escitalopram/tDCS-sham (n=75), tDCS/placebo-pill (n=75), or placebo-pill/sham-tDCS (n=45). General linear models assessed the interaction between treatment group and allele-wise carriers. Additional analyses were performed for each group and each genotype separately. Results: Pairwise group comparisons (tDCS vs. placebo, tDCS vs. escitalopram, and escitalopram vs. placebo) did not identify alleles associated with depression improvement. In addition, exploratory analyses also did not identify any SNP unequivocally associated with improvement of depression in any treatment group. Conclusion: Larger, combined datasets are necessary to identify candidate genes for tDCS response.